The Power of Weather: Some Empirical Evidence on Predicting Day-ahead Power Prices through Day-ahead Weather Forecasts - Christian Huurman; Francesco Ravazzolo; Chen Zhou (Tinbergen Institute, 2007)
In the literature the effects of weather on electricity sales are well-documented. However, studies that have investigated the impact of weather on electricity prices are still scarce (e.g. Knittel and Roberts, 2005), partly because the wholesale power markets have only recently been deregulated. We introduce the weather factor into well-known forecasting models to study its impact. We find that weather has explanatory power for the day-ahead power spot price. Using weather forecasts improves the forecast accuracy, and in particular new models with power transformations of weather forecast variables are significantly better in term of out-of-sample statistics than popular mean reverting models. For different power markets, such as Norway, Eastern Denmark and the Netherlands, we build specific models. The dissimilarity among these models indicates that weather forecasts influence not only the demand of electricity but also the supply side according to different electricity producing methods.
Keywords: C53; G15; Q40; 330; Electricity prices; forecasting; GARCH models; weather forecasts; Strompreis; Prognoseverfahren; Meteorologie; Wetter; ARCH-Modell; Norwegen; Dänemark; Niederlande